2023
DOI: 10.55563/clinexprheumatol/nat8nl
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the management of rheumatoid arthritis: one year in review 2023

Abstract: New evidence from 2022 slightly changed some perspectives for rheumatoid arthritis (RA) management. Realworld data on the efficacy and safety of disease-modifying anti-rheumatic drugs strengthened the importance of tailoring treatment decisions based on patient characteristics. Moreover, the research of response biomarkers to therapy underlined the need for precision medicine and remote care applications showed an innovative outlook that supports a patient-centred approach. New developments in vaccinations led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Male sex was the only predictor associated with reaching SR in our study. Male sex being a predictor of remission was also recently highlighted in a review by Garaffoni et al (39). Favalli et al showed that disease activity is higher and response to b/tsDMARDs is lower in women compared to men, which might explain the lower remission rates (40).…”
Section: Univariable Analysis Multivariable Analysismentioning
confidence: 91%
“…Male sex was the only predictor associated with reaching SR in our study. Male sex being a predictor of remission was also recently highlighted in a review by Garaffoni et al (39). Favalli et al showed that disease activity is higher and response to b/tsDMARDs is lower in women compared to men, which might explain the lower remission rates (40).…”
Section: Univariable Analysis Multivariable Analysismentioning
confidence: 91%
“…Following our regular annual reviews on different aspects of rheumatology (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) we will here provide a critical digest of the recent literature on Ax-SpA of 2021 and 2022 (Medline search of articles published from 1st January 2021 to 31th December 2022). In particular, we performed an on-line search on MESH database, using as key terms "blood", "chemistry", "diagnosis", "diagnostic imaging", "drug therapy", "epidemiology", "metabolism",…”
Section: Methodsmentioning
confidence: 99%
“…When inadequately treated or refractory to standard treatments, IAs may lead to disability, impairment of health-related quality of life, and an increase in mortality. To date, treating rheumatologists have access to several effective disease-modifying anti-rheumatic drugs (DMARDs) approved for RA and PsA (conventional synthetic (cs), biological (b), and targeted synthetic (ts) DMARDs) ( 3 , 4 ). Most treatments are efficacious in different diseases, but still have a relevant proportion of failures, or suboptimal responses ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%